Utilization of Areca Nut Fibers (areca catechu l.) and Polyvinyl Chloride (PVC) as A Sound Absorbing Material - Nurul, Nurul Mutaharah; Rauf, Nurlaela (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
Noise refers to unwanted sounds emanating from production equipment or work equipment, which are potentially harmful. The most common factor affecting workers is noise, which can impair hearing. The impact can be both psychological and biological problems. To solve this problem, noise-absorbing materials that can be installed in various places are needed. One of the proposed solutions is the development of acoustic materials made from easily available natural fiber composites, such as areca nut fibers. Areca fibers are integrated as a base material for acoustic materials that aim to reduce outdoor noise or from building structures. In this study, 2 testing methods were carried out, namely the Sound Absorption Coefficient (α) Test and the Fourier Transform Infrared (FTIR) Test. The Sound Absorption Coefficient Test aims to measure the ability of materials to absorb sound energy, while FTIR is used to analyze sample components without damaging them. The sound absorption coefficient test results showed that the samples were able to absorb sound at a frequency of 800-1600 Hz. After the areca fiber was treated with NaOH, there was a change in the O-H group which indicated a reduction in lignin content in the areca fiber. This O-H group shift causes an increase in adhesion between the matrix and filler in the composite.